Bio-Derived Materials and Their Application in Water Purification (International Journal of Communication Systems and Network Technologies, 2023)
The scarcity of clean and safe drinking water is one of the major problems faced by human nowadays. The study is focused on the filtration of domestic waste water. This filtration is done by preparing here different bed using different layers of powdered cactus, pine bark, sand and coarse aggregate. The use of pine bark enhances the purification by preventing microbial action and reduces turbidity. But the application of the pine bark increases the concentration of acidity. In order to reduce the acidity, coarse aggregate is used as another layer. Finally, a sandy layer is provided as a supporting layer for powdered cactus. The thickness was fixed by column study method. As per the column study, we fixed different layers for different filter bed (f1 f2 f3) consist of F1: 3cm pine bark and 3cmcactus powder F2: 3cm pine bark and F3: 5cm pine bark and 5cm cactus powder. The percentage reduction for Turbidity, Alkalinity, Hardness, Chloride, Acidity, BOD for F3 were obtain 56%, 13%, 43%, 85%, 58%, 84% respectively.
Keywords: Grey Water; Pine Bark; Cactus Powder; Filtration; Turbidity; BOD; Water Purification